The Effect of Hypoglicemia on Criminal Liability In Diabetic Patients - Kaynak, Ayşe Derya; Tümer, Ali Rıza (The Bulletin of Legal Medicine, 2019)
It is common for people who are charged with crime to assert that their will is not in place during the action of the crime by asserting health problems in their defense to avoid unfair penal sanctions. In this regard, mental health disorders are the most common. However, other health problems affecting the state of consciousness should not be forgotten. Diabetes patients may also claim that their will is disabled in the crimes committed in the attack of hypoglycemia. There are also known chronic complications such as vision loss, renal failure, heart attack, personality changes in long-term diabetes patients, as well as acute treatment complications such as hypoglycemia and neuroglycopenia, which are caused by high-dose insulin therapy and are characterized by impaired cognitive functions. The courts can therefore request expert opinion from the forensic experts on the determination of the person's criminal liability. In this article, it is aimed to discuss the cases of hypoglycemia and neuroglycopia, which is a common treatment complication in diabetic patients, and whether or not cognitive and cognitive disorders in the individual can affect criminal responsibility, and if so, the extent to which these effects may affect the case.
Keywords: patients with diabetes; criminal discretion; criminal responsibility; behaviour